Time-Dependent Density Functional Theory Calculations of N- and S-Doped TiO2 Nanotube for Water-Splitting Applications - LIN, YIN-PAI; Isakoviča, Inta; Gopejenko, Aleksejs; Ivanova, Anna; Začinskis, Aleksandrs; Eglitis, Roberts; D’Yachkov, Pavel N.; Piskunov, Sergei (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
On the basis of time-dependent density functional theory (TD-DFT) we performed first-principle calculations to predict optical properties and transition states of pristine, N-and S-doped, and N+S-codoped anatase TiO2 nanotubes of 1 nm-diameter. The host O atoms of the pristine TiO2 nanotube were substituted by N and S atoms to evaluate the influence of dopants on the photocatalytic properties of hollow titania nanostructures. The charge transition mechanism promoted by dopants positioned in the nanotube wall clearly demonstrates the constructive and destructive contributions to photoabsorption by means of calculated transition contribution maps. Based on the results of our calculations, we predict an increased visible-light-driven photoresponse in N-and S-doped and the N+S-codoped TiO2 nanotubes, enhancing the efficiency of hydrogen production in water-splitting applications. © 2021 by the authors. Licensee MDPI, Basel, Switzerland. The article is published under the CC BY 4.0 license.
This research was funded by the Latvian Council of Science grant LZP-2018/2-0083. Institute of Solid State Physics, University of Latvia, as the Center of Excellence, has received funding from the European Union?s Horizon 2020 Framework Program H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under Grant Agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES; Absorption spectra; Photocatalyst; Time-dependent density functional theory; TiO2 nanotube; Transition contribution maps